CONCEPTION-ADOPTION MODEL OF ORGANIC RICE INNOVATION: FARMERS SOCIAL ECONOMY (CASE STUDY IN TASIKMALAYA, WEST JAVA) - Heryanto, Mahra Arari (Journal of S&T Policy and R&D Management, 2014)
The process of organic rice farming system conception initiated by inter-national market demand for organic rice which is drive businessman to create a partnership with farmer to fullfil the demand. In conception stage, it is running effectively substitue convetional farming with organic farming system. However, conception process which has been running will not continue to adoption stage if this process managed not properly. Social factor (farmer behaviour)is a determinant in farmer decision to adopt organic farming system because of interelations with the economic practically. Technology, environment, attitude and belief interaction in adoption stage more complex than canception stage. This model built qualitatively using system thinking method and social fabric matrix (SFM). Causal loop diagram used to analyze causality of elements interalistionship in conception and adoption stage, thus social fabric matrix used to mapping the element interelation involved in organic farming adoption which is consist of social institution, technology, environment, value and belief, and attitude. This research indicates that adoption stage is critical point that have to be passed in an innovation process. The point is innovation should be managed properly since the conception until adoption that involved social, economy and technology elements.